2015
DOI: 10.4137/vrt.s31744
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Hepatitis B Virus, Hepatitis C Virus, and Different Clinical Parameters in the Thalassemic Population of Capital Twin Cities of Pakistan

Abstract: Hepatitis B and C are serious public health problems worldwide. Thalassemia patients are dependent on blood transfusions throughout their life and are at high risk of viral infections. The aim of this study was to estimate the prevalence of hepatitis B/C infections and different clinical parameters in multitransfused thalassemia population. In this study, 262 multitransfused β-thalassemia patients were enrolled from the capital twin cities of Pakistan. The presence of hepatitis B virus (HBV)/hepatitis C virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…Hepatitis C virus (HCV) is blood borne pathogen which causes severe liver disorders, including hepatocellular carcinoma (HCC), hepatic steatosis, liver cirrhosis, end stage liver disease and various metabolic disorders (Saeed et al, 2014(Saeed et al, , 2015. In 1975 hepatitis C virus (HCV) was initially recognized as non-A, non-B viral hepatitis (NANBH).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) is blood borne pathogen which causes severe liver disorders, including hepatocellular carcinoma (HCC), hepatic steatosis, liver cirrhosis, end stage liver disease and various metabolic disorders (Saeed et al, 2014(Saeed et al, , 2015. In 1975 hepatitis C virus (HCV) was initially recognized as non-A, non-B viral hepatitis (NANBH).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that more than 21204 people were infected with dengue in November 2010 after a worst flood in Punjab [11] . The prevalence of viral infections is unfortunately increasing day by day in developing countries due to limited awareness among the general population [12,13] . Although a new vaccine for dengue fever has proven safe in nonhuman primates, a lot of efforts are required to supply effective vaccines at minimal cost.…”
Section: To the Editormentioning
confidence: 99%
“…[ 12 ] Epidemiologic studies revealed that 4.5% (Turkey[ 13 ]) to 91.8% (Romani[ 14 ]) of thalassemia patients have HCV infection. [ 15 16 17 18 19 ] In Iran, the prevalence of thalassemia is relatively high and previous studies reported HCV infection in 13.6%,[ 20 ] 19.3%,[ 21 ] 26.9%,[ 22 ] to 39.7%[ 23 ] in Iranian thalassemia patients.…”
Section: Discussionmentioning
confidence: 99%